Unfinished Turns in French: How Context Matters - Chevalier, Fabienne HG (Lawrence Erlbaum Associates, 2008)
On occasions, speakers do not complete their turns in conversation. Such syntactically-incomplete turns are not treated with repair or misunderstanding. The responses that they receive display a clear understanding of the actions that the unfinished turns embodied. In this article, using conversation analysis (CA), I describe the systematic occurrence of unfinished turns in French conversation. I show that context is necessary to the understanding of this type of turn and I describe the nature of that context. Data analysis reveals that unfinished turns are understandable primarily by reference to their sequential position. I conclude that unfinished turns are a locally- managed resource fitted to the particulars of the talk in progress and built upon the context that the sequences that house them have so far provided.